The contribution of formation by alternation in thesuccession of family farming - Hillesheim, Luis Pedro; Vizzotto, Mateus (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In 2002 it was established the Rural Family House Santo Isidoro (CFRSI) in Frederico Westphalen, Rio Grande do Sul Stateaiming to raise the quality of life in the field and tocreate conditions for the young people remain and develop rural areas. The CFRSI educates and qualifies young people through the Pedagogy of Alternation. From 2002 to 2013 were formed 10 classes with a total of 151 young family farmers. In this study, we aimed to identify what motivated them to look for a school that offers a differentiated formation and which elements allows to visualize the relationship between their Life Professional Project and their permanence in rural areas. In additionto the integral formation, the goal of the CFRSI is to create opportunities for the young to develop their farms, and to improve their incomes and the family's quality of life. The findings show that 90% of the young that received formation at CFRSI still live in the rural areas, and of these 22% have activities outside the farm but still live in the rural areas, but only 10% left the rural areas. We also find that the reason that most contributes to the rural exodus is the economic insecurity and the resistance of the other family members to the deployment of their Life Professional Project.